THE IMPACT OF AN EDUCATIONAL PROGRAM THAT USES SMARTPHONE APPS TO ENHANCE THE SKILL OF MEMORIZING THE HOLY QURAN BY FEMALE STUDENTS (ADULTS) IN THE HOLY QURAN SCHOOL IN THE EAST OF RIYADH - Al-abbasi, Daniah Abdulaziz; Al-lefan, Mshael Abdulrahman (Journal of Educational and Psychological Sciences, 2019)
This study is designed to identify the impact of an educational program that uses smartphone apps for learning the Holy Quran by female students (adults) and measure their satisfaction compared to the conventional method of learning. The Quasi-experimental approach was used. The sample of the study consisted of 31 female students (adults,18-50 years old) in the Holy Quran School in the east of Riyadh for the first semester of the scholar year 1439/1440 AH. The participants were selected deliberately. The first group (the control group) consisted of (14) female students and the second group (the experimental group) consisted of (17) female students according to the method of the designed program. Oral testing was used as a key tool for data collection, while the questionnaire was used as a further tool of the study to identify the satisfaction of students. The results of the study showed that the experimental group scored (32.73), while the control group scored (26.53). The difference was statistically significant at 0.05 and less in the oral testing in favor of the experimental group. The educational program met a high percentage of students' satisfaction, where the average of questionnaire tool reached 4.41 out of 5. At the level of the topics, the "performance level" reached the highest average (4.48), followed by "the level of meeting user's expectations" with an average of 4.47, and finally the "Students' attitudes towards the use of smartphone apps in the learning the Holy Quran" with an average of 4.26. In the light of the results, a set of recommendations and proposals were suggested to promote smartphone apps in the memorization of the Holy Quran.
Keywords: Impact; educational program; smartphone; the skill of memorization; female students (adults)